The maturity levels of the digital technology competence in vocational education - Melinda Astuti; Zainal Arifin; Muhammad Nurtanto; Farid Mutohhari; Warju Warju (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study aimed to analyze the maturity level of teachers and vocational students. It also measured differences in the maturity level of teachers and vocational students in mastering the digital technology competence (DTC) in vocational education. Quantitative research used a design developed by Hoy and Adams. A total of 233 respondents came from public and private schools in vocational schools in Yogyakarta, Indonesia. Data was collected using a Likert scale questionnaire (1-4). The data were analyzed by descriptive statistics and inferential statistics with one-way analysis of variance (ANOVA). The results on the maturity level of vocational teachers obtained a score of 13.16-23.68 in the "Low" category and for vocational students obtained a score of 12.98-22.12 in the "Low" category, and there was no significant difference. Teachers and students in vocational schools must have awareness in improving digital technology capabilities at the criticism technology level.